The role of protein kinase C in platelet activation - Unsworth, AJ (2012)
The protein kinase C (PKC) superfamily is a key regulator in platelet activation with individual isoforms playing distinct roles. This thesis focuses on the role of the novel PKC isoforms downstream of several agonists using both pharmacological and genetic approaches and human and mouse platelets. Quantification of the protein levels of PKC isoforms identified different levels of the five major PKC isoforms expressed in human platelets and also differences between levels of the same isoform in human and mouse platelets. Use of a selection of broad spectrum and isoform-specific inhibitors, identified both positive and negative novel roles for PKC in the regulation of human and mouse platelets. A net positive role for PKC was found in GPVI, Clec-2, and PAR receptor signalling, with classical isoforms of PKC playing a major role in aggregation and dense granule secretion. A novel negative regulatory role was also identified in the regulation of ADP-induced platelet activation for PKCβ, and both PKCε and PKCβ in human and mouse platelets respectively. Gene knock-out mouse models confirmed a positive regulatory role for PKCθ in αIIbβ3 outside-in signalling but identified no other regulatory role for PKCθ in agonist induced platelet activation. Despite this relatively minor role, functional redundancy was identified between PKCθ and PKCε isoforms in haemostasis, as tail bleeding was significantly increased in mice deficient in both novel isoforms. The work presented here identifies key roles for the PKC superfamily in the complex regulation of platelet activation, with different isoforms supporting and limiting the process of thrombus formation and haemostasis.